A COMPARATIVE STUDY OF MORPHOSYNTACTIC CLASSIFICATION OF LEXICAL CATEGORIES IN ENGLISH AND UZBEK (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a comparative linguistic analysis of the classification of parts of speech in English and Uzbek. The study explores the morphological, syntactic, and semantic criteria used in categorizing words into different parts of speech in both languages. It highlights similarities and differences in the traditional and modern linguistic approaches, considering the influence of typological features, historical development, and structural characteristics of English and Uzbek. The analysis aims to contribute to a deeper understanding of cross-linguistic grammatical frameworks and offers insights for language learners, teachers, and researchers involved in comparative linguistics and translation studies.